VD_FINDINFO AI 230/13 - 11/2015 vom 15. Januar 2015 - VD Tribunal cantonal (2015)
RENTE D'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ, ÉTAT DE SANTÉ, REVENU D'INVALIDE | 28 al. 1 LAI, 17 al. 1 LPGA, 6 LPGA, 7 LPGA, 8 LPGA, 88a al. 1 RAI